Implementation of modern therapy approaches and research for non‐small cell lung cancer in Japan. Issue 2 (February 2015) - Nakanishi, Yoichi
Abstract The genetic backgrounds of the Japanese (or Asians) are, at least in part, different from those of Caucasians. It is necessary to recognize this difference to develop medicine that is both optimized and individualized. In particular, the consideration of ethnic differences is becoming increasingly important for lung cancer medicine. Japanese clinical practice guidelines indicate that some clinical biomarkers, such as epidermal growth factor receptor gene mutations, echinoderm microtubule‐associated protein‐like 4‐anaplastic lymphoma kinase fusion gene and uridine diphosphate glucuronosyltransferase genotypes should be determined in appropriate lung cancer patients. At the present time, tests for these biomarkers are covered by the Japanese national health‐care programme, as is treatment with certain targeted drugs and cytotoxic agents. Therefore, most patients with lung cancer in Japan receive these tests as part of daily practice if their performance status and organ function are judged to be eligible. In addition, ethnic differences in bone marrow toxicity caused by cytotoxic drugs are reflected in treatment choice, and the requirements for the development of treatment modalities suitable for rare targeted populations are also increasing. To meet these requirements, many collaborative groups in Japan that have improved their infrastructure for investigator‐initiated trials and conducted important activities need to provide further optimal treatment modalities for Japanese and Asian patients with lung cancer. Here, the characteristics of lung cancer in Japanese patients, general aspects of medical treatment and the care system in Japan, and representative studies on lung cancer in Japan are reviewed.